Attacking and Exploiting Modern Web Applications : Discover the mindset, techniques, and tools to perform modern web attacks and exploitation /: Discover the mindset, techniques, and tools to perform modern web attacks and exploitation. (2023) - Onofri, Simone; Onofri, Donato
No abstract available